HISAB AWAL WAKTU SALAT DALAM KITAB AL-KHULASAH FI AL-AQWAT AL-SYAR’IYYAH BI AL-LUGHARITMIYYAH KARYA MUHAMMAD KHUMAIDI JAZRY - Mubit, Rizal (Ahkam: Jurnal Hukum Islam, 2016)
Prayer is the pre-determined-timed obligatory worship. The jurists decide the time of prayer based on the rotation of the earth or natural phenomena. Such concept is still thought to be applicable until today. On the contrary, the astronomers decide the time of prayer based on a more mathematical formula. Since the invention of arithmetic, prayer time decision formula and methods are always evolving until now. Good progress occurs in the formula as well as in the use of tools. There are several methods used by the experts to confirm it. One is the concept of the calculation using logarithm tables. The book that discusses the methods is the book Al-Khulasah fi al-Awqat al-Syar’iyyah bi al-Lugharitmiyyah by Muhammad Khumaidi Jazry. In this book, in addition to making the calculation formula, the author also specifies the use of a table of five decimal logarithms. The results compared with calculations using the ephemeris method do not produce a significant difference. The difference between every prayer time is only in the range of two to four minutes. Kata kunci: Waktu Salat, Tabel Logaritma, Al-Khulasah fi Al-Awqat al-Syar’iyyah bi al-Lugharitmiyyah